Peningkatan Kemandirian Petani Nenas dalam Penanganan Mesin Produksi Vacuum Frying di Desa Kualu Nenas - Nofirza Nofirza; Merry Siska; Wresni Anggraini (Lembaga penelitian dan pengabdian kepada masyrakat, 2012)
The farmer groups in Kualu Nenas village has acquire many assists from local government and other sectors as a part of comunity development program. The assist include production machines, like vacuum frying, press seal machine, cutting machine, etc, also workshop about the machinary and the production proccess. But now, many of those aids become useless and infertile, because of the incapable of the farmers to maintenance those machines. The empowerment become an important issue since the machine’s price moderatly expensive. The focus of this research is to conduct and evaluate the machine vacuum frying workshop of the introduction and it maintenance for the farmer’s groups of Kualu Nenas. Using the Participatory Action Research (PAR) method which is a basic research that provide the community empowerment, do some strategies/ steps: (i)Information explore and community approach, (ii)The Workshop accomplishment, and (iii)Program’s evaluation. The result is seen good enough but after analyzing, the workshop of the machine maintenance not too efective to answer the needs of the farmer in handling the machine’s damage or troubeshooting. One of the reason is because it just did once and some still doubt to do it if there is no companion. The summary of the evaluation is that the workshop will not be effective if not following by the continuing companion until they really become empower and capable in looking for solution to face the production machine problem.